COMPARATIVE ANALYSIS OF TALAQ THAT PASSED OUTSIDE THE COURT IN THE PERSPECTIVE OF ISLAMIC LAW AND COMPILATION OF ISLAMIC LAW - Zahir, Irham (Institut Agama Islam Negeri Bone, 2021)
Talaq is a termination of marital status which is prescribed under certain conditions, and its procedure has been regulated, both in Islamic Law and in the compilation of Islamic Law (KHI). This is library research which focused on library materials using a qualitative descriptive approach that leads to the textual juridical of Islamic Law and KHI, and examines what has been set in Islamic Law and from various books; then compared with the KHI so that can find out the differences and common ground between the two legal systems then can be a basis to be applied.By using this research method, it is concluded that the Law of fiqh allows talaq divorce based on the willingness of both parties or on the initiative of the husband/wife unilaterally. In fact, talaq divorce can be done without interference from the judiciary. Whereas in the rules of the Compilation of Islamic Laws, talaq outside the Court is not valid according to the perspective of Law No.1 of 1974 on Marriage and the Compilation of Islamic Law (KHI), although fiqh allows talaq outside the Court, it has no power in positive Law.